2008
DOI: 10.1111/j.1475-6773.2008.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Patient Safety Climate in the VA

Abstract: Objective. To assess variation in safety climate across VA hospitals nationally. Study Setting. Data were collected from employees at 30 VA hospitals over a 6-month period using the Patient Safety Climate in Healthcare Organizations survey. Study Design. We sampled 100 percent of senior managers and physicians and a random 10 percent of other employees. At 10 randomly selected hospitals, we sampled an additional 100 percent of employees working in units with intrinsically higher hazards (high-hazard units [HHU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
64
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 36 publications
(37 reference statements)
11
64
1
Order By: Relevance
“…137,143 Our findings broadly support existing research that shows a more positive assessment of safety climate by managers than by clinical staff. 37,102,103,229,230 The teamwork climate 25 results, but not other components of the survey-based safety climate measure, accord with other studies that found nurses' assessments of aspects of safety climate more negative than doctors' assessments. 106,218,228 To what extent might the empirical results be considered predictable?…”
Section: Comparison Correlation Agreementsupporting
confidence: 77%
“…137,143 Our findings broadly support existing research that shows a more positive assessment of safety climate by managers than by clinical staff. 37,102,103,229,230 The teamwork climate 25 results, but not other components of the survey-based safety climate measure, accord with other studies that found nurses' assessments of aspects of safety climate more negative than doctors' assessments. 106,218,228 To what extent might the empirical results be considered predictable?…”
Section: Comparison Correlation Agreementsupporting
confidence: 77%
“…Operating room (OR) safety has increased but the literature suggests that opportunities for improvement remain (Alfredsdottir & Bjornsdottir, 2008;Christian et al, 2006;Hartmann et al, 2008;Lingard et al, 2008). Three ways that intraoperative safety has been increased are through improvements in equipment (Barnett & Nathoo, 2004;Kaibara, Saunders, & Sutherland, 2000), individual provider training (Awad et al, 2005;Buback, 2004;Makary et al, 2007), and operative team functioning (Einav et al, 2010;Gore et al, 2010;Haynes et al, 2009;Manser, 2009;Mazzocco et al, 2009;Wolf, Way, & Stewart, 2010).…”
mentioning
confidence: 99%
“…Multiple studies that assessed climate and patient care in hospital environments (Hansen, Williams & Singer, 2011; Hartmann et al, 2008; Rosen et al, 2010; Singer et al, 2009) found that senior management routinely rated the hospital climate higher than frontline staff. However, frontline staff perceptions were more closely associated with patient readmission and compromised patient safety than senior management perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Frontline staff members were more accurate than senior management in identifying weaknesses in safety climate associated with worse patient outcomes. Consistently, staff with direct contact with patients had the most exposure to potential safety issues and resultantly had significantly higher levels of problematic response compared to senior managers, whose work is removed from the direct patient care environment (Hartmann et al, 2008). As senior managers are less often exposed to frontline work, they may be less informed about safety performance than frontline workers whose actions directly affect patients; this is true regardless of health care systems or settings (Rosen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%